2021
DOI: 10.4103/npmj.npmj_554_21
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Practices Towards COVID-19 Amongst Residents in Southern Nigeria

Abstract: Background: Within a short duration, coronavirus disease 2019 (COVID-19) spread globally, affecting all facets of life and causing widespread panic. This study set out to assess the perception and practices towards COVID-19 of urban and rural residents in Akwa Ibom State, Nigeria. Materials and Methods: A cross-sectional study design and multistaged sampling technique were used. Data were collected using an interviewer-administered questionnaire between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…According to this study, urban residents’ pregnant women were 2.24 times more likely than pregnant women in rural residents to have a high-risk perception. Studies in the United States (Chauhan et al 2021 ) and Nigeria (Akwaowo et al 2021 ) supported this evidence. High levels of information and risk cognition regarding COVID-19 among urban residents (Ripon et al 2021 , Rahman et al 2021 ) lead to a high level of risk perception; hence, those more knowledgeable about the outbreak are more concerned about being infected during the pandemic (Vartti et al 2009 ).…”
Section: Discussionmentioning
confidence: 85%
“…According to this study, urban residents’ pregnant women were 2.24 times more likely than pregnant women in rural residents to have a high-risk perception. Studies in the United States (Chauhan et al 2021 ) and Nigeria (Akwaowo et al 2021 ) supported this evidence. High levels of information and risk cognition regarding COVID-19 among urban residents (Ripon et al 2021 , Rahman et al 2021 ) lead to a high level of risk perception; hence, those more knowledgeable about the outbreak are more concerned about being infected during the pandemic (Vartti et al 2009 ).…”
Section: Discussionmentioning
confidence: 85%
“…Another event contributing to the negative perception and neglect of the virus is hunger and starvation. According to [34], the effects most frequently reported by respondents (360) were hunger/low income (48.8%) and academic delay (8.8%).…”
Section: People's Perceptions On Covid-19 In Nigeriamentioning
confidence: 99%
“…In a study by [39], it was observed that the general perception of Nigerian youths about the health system and Government handling of the COVID-19 was poor. The research work by [34] revealed that out of a sample of 350 respondents, the following perceptions were observed: 95% of the respondent would go to the hospital if they noticed the development of any COVID-19 symptoms. In contrast, 58.3% agreed to call the COVID-19 helplines.…”
Section: People's Perceptions On Covid-19 In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Structural inequalities, vaccine apartheid and resource limitations are some factors affecting the COVID-19 response in sub-Saharan African countries [4]. While studies have evaluated public perceptions of pandemic risk and health protective behaviors in Nigeria [5], little is known about the factors that impact COVID-19 mortality in this country. Within rural areas, factors such as health center availability, transportation, and infrastructure challenges may render populations more vulnerable to disease [6].…”
Section: Introductionmentioning
confidence: 99%